Sistem Saringan Autisme - Muhammad Mizi Magendran, Nur Athirah Syahin; Hassan, Norlida (Applied Information Technology And Computer Science, 2021)
The Autism Screening System is a web-based system that aims to assist parents in obtaining guidance and information to perform autism screening on children. This Autism Screening System aims to assist parents in making autism screening for children aged 18 to 36 months, with a simpler method and only requires a few clicks. Many parents are not exposed to the characteristics of autism or things that show signs of autism. The system also makes it easier for parents who do not have the opportunity to screen their children in the hospital. This screening can be done online only without face-to-face with an expert. The system is developed using Hypertext Markup Language 5 (HTML5), HyperText Pre-Processor (PHP) as a server-side scripting language. Sublime Text 3 is used as the encoding editor software. All user and administrator data will be stored in a MySQL database. Observation and research are used as a method in collecting information about childhood autism to ensure that all information obtained is accurate as a source of parental guidance. The Prototype model is used as a well-run system development methodology. These phases help in ensuring that the system development journey is more orderly and more suitable to be used to assist the system development process. The Autism Screening System will make it easier for parents to talk about their children’s activities and development to do physical activities better.